2019
DOI: 10.1021/acsomega.9b01413
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Histone Methylation (H3K9me3) Changes in Live Cells

Abstract: H3K9me3 (methylation of lysine 9 of histone H3) is an epigenetic modification that acts as a repressor mark. Several diseases, including cancers and neurological disorders, have been associated with aberrant changes in H3K9me3 levels. Different tools have been developed to enable detection and quantification of H3K9me3 levels in cells. Most techniques, however, lack live cell compatibility. To address this concern, we have engineered recombinant protein sensors for probing H3K9me3 in situ. A heterodimeric sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 63 publications
2
37
0
Order By: Relevance
“…We quantified changes in H3K9me3 by measuring the I ntegrated I ntensity per N uclei (IIN). We and others have previously demonstrated that IIN correlates with global epigenetic modification level per cell ( Sanchez et al, 2017 , Sánchez et al, 2019 , Sánchez et al, 2020 , Lungu et al, 2017 , Hayashi-Takanaka et al, 2011 ). IIN analysis between the control and Pb-treated groups shows that Pb exposure significantly ( p < 0.05, one-way ANOVA followed by Tukey’s HSD post-hoc test) lowers the global level of H3K9me3, by 16% and 36% for Pb concentrations of 100 and 500 ppb, respectively (see Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…We quantified changes in H3K9me3 by measuring the I ntegrated I ntensity per N uclei (IIN). We and others have previously demonstrated that IIN correlates with global epigenetic modification level per cell ( Sanchez et al, 2017 , Sánchez et al, 2019 , Sánchez et al, 2020 , Lungu et al, 2017 , Hayashi-Takanaka et al, 2011 ). IIN analysis between the control and Pb-treated groups shows that Pb exposure significantly ( p < 0.05, one-way ANOVA followed by Tukey’s HSD post-hoc test) lowers the global level of H3K9me3, by 16% and 36% for Pb concentrations of 100 and 500 ppb, respectively (see Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Z-stack images of cells were collected using Nikon EZ-C1 software. Collected images were analyzed using Cellprofiler ( Carpenter et al, 2006 ) to get the I ntegrated I ntensity per N uclei (IIN) as we detailed in our previous work ( Sanchez et al, 2017 , Sánchez et al, 2019 , Sánchez et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor for histone H3K9me3 based on a chromodomain was also reported. 54 These sensors could be coupled to a DNA-binding zinc finger domain to monitor locusspecific H3K9me3 modification, 55 or to other histone reader domains to simultaneously report multiple histone modifications, 56,57 or with a methyl binding domain to simultaneously visualize 5-methylcytosine. 57 Further strategies to visualize histone proteoforms involve creation of FRET-based sandwich sensors through strategic fusion of the PTM recognition domain and the histone protein in between a fluorescent protein FRET pair (Fig.…”
Section: Molecular Tools To Detect Proteoforms Involving Addition Of Functional Groupsmentioning
confidence: 99%
“…The detection of epigenetic changes by protein-based fluorescent probes allows for real-time analysis of the changes to the global epigenome levels. So far protein probes have been developed for binding and visualization of both DNA methylation and histone modifications ( Hendrich and Bird, 1998 ; Lungu et al, 2017 ; Sanchez et al, 2017 ; Sanchez et al, 2019 ). Further development of nanobody fragments have provided an additional domain that allows for high specificity and affinity for selected epigenetic targets ( Hattori et al, 2016 ; Jullien et al, 2016 ).…”
Section: Assess Neurotoxicity Using Cell Cultur Modelmentioning
confidence: 99%